Remoção de hidrocarbonetos policíclicos aromáticos por substratos sólidos estudos com amberlite XAD-2, polietileno, poliuretano, sílica e fibra de quartzo - Silva Junior, Fabio Vieira da (2013)
Polycyclic aromatic hydrocarbons (PAHs) are a class of compounds characterized by having two or more condensed aromatic rings. These substances, as well as their nitrated and oxygenated derivatives, can be found widely spread as constituents of complex mixtures in the environment. A variety of PHAs, in many cases showing similar structures, can be found in the environment. The United States Environmental Protection Agency (U.S. EPA) has listed 16 PAHs based on their toxicological profiles, as priority pollutants. In the present study, the performance of the solid substrates Amberlite XAD-2, polyethylene, high-density polyurethane foam, silica gel and quartz fiber were investigated as alternative to XAD-2 to remove HPAs from solutions. The investigation of the adsorption of naphthalene, acenaphthylene, acenaphthene, fluorene, phenanthrene, anthracene and chrysene was conducted in aqueous solutions by batch experiments, considering the initial concentrations of substrates and PHAs, time, temperature and influence of cosolvency. Spectrophotometry and liquid chromatography with UV detection were used to assess the removal yield. The results showed that the yields of PAH strongly dependent on the substrate as well as the PHA. The PAHs were most quickly and almost totally (except chrysene and anthracene) removed by polyurethane foam. High density polyethylene behaves similarly to XAD-2. Among the investigated PHAs, chrysene showed a different behavior, since the best adsorbents for this compound were as silica gel and quartz fiber. Thus the personal samplers for PHAs must be prepared as a mix of adsorbents instead of having a unique composition.